Menarche age and satisfaction with body weight - Nivia Marcia Velho; Edio Luiz Petroski; Maria Ferminia Luchtemberg De Bem (Universidade Federal de Santa Catarina, 1999)
This study aims to characterize sexual maturation through menarcheal age and the level of satisfaction with body mass, in students studying at public schools in Florianopolis and adjoining areas of the State of Santa Catarina, Brazil. The research project enrolled 1070 students of puberty age from 33 schools in 11 different towns. Menarcheal age (MA) was determined using the retrospective method and converted into decimal age. Results demonstrated that mean MA was 12.56 years of age median MA was 12.54 years. Adolescents with earliest and latest sexual maturation were 9.11 and 15.63 years of age, respectively. 51.8% of the adolescents were satisfi ed with their body mass and 48.2% were unsatisfi ed. The stated reasons for the dissatisfaction were : 1st - 74.2% of the adolescents believed they were overweight and would like to lose some weight. 2nd - 20.2% believed they were underweight and would like to put some on. 3rd - 5.6% described reasons of an aesthetic nature. Analysis of the results suggests the following conclusions: a) The mean MA of these students from Santa Catarina state public schools was 12.56 years of age; b) Those students who were not happy with their body mass and wished to lose weight had matured earlier, which was exactly the opposite of those students who were satisfi ed; c) There was a tendency towards later MA when students came from larger families, smaller towns and lower socioeconomic classes; d) There is a tendency towards earlier MA when students come from smaller families, bigger towns and higher social classes. RESUMO O propósito deste estudo foi caracterizar a maturação sexual através da idade de menarca (IM) e a satisfação com a massa corporal em escolares da rede pública Estadual de Ensino da Grande Florianópolis, SC. Participaram da amostra 1070 adolescentes de 33 Unidades de Ensino, procedentes de 11 municípios. A IM foi determinada através do método retrospectivo e convertida em idade decimal. Os resultados mostraram média para a IM de 12,56 anos e mediana de 15,54 anos. As adolescentes com maturação sexual mais precoce e mais tardia foram de 9,11 e 15,63 anos, respectivamente. Estão satisfeitas com a massa corporal 51,8% das adolescentes e insatisfeitas 48,2%. Os motivos indicados para a insatisfação com a massa corporal foram: 1º) 74,2% das adolescentes julgavam-se com sobrepeso e gostariam de perdê-lo; 2º) 20,2% julgavam-se com baixo peso e gostariam de ganhá-lo; e, 3º) 5,6% indicaram motivos de ordem estética. A análise dos resultados sugeriu as seguintes conclusões: a) a IM das escolares da Grande Florianópolis ocorre em média aos 12,56 anos; b) escolares insatisfeitas com a sua massa corporal, e que desejam perder peso, maturam mais precocemente do que as satisfeitas com a massa corporal. c) a IM tende ser mais tardia quando as escolares são oriundas de famílias grandes, de centros urbanos menores e de nível sócio-econômico baixo; d) a IM tende a ser mais precoce quando as escolares são oriundas de famílias pequenas, de centros urbanos maiores e de nível sócio-econômico alto.